Efeitos da laserterapia e do Exercício Físico na dor neuropática pós-traumática em ratos - CUTRIM, Jorge Roberto Baldez (2022)
Neuropathic (DN) pain is caused by a lesion or disease of the somatosensory nervous system, which affects about 8% of the world's population, and its management is considered a major challenge, due to the complexity and absence of specific pharmacological and conservative treatments. The objective of this study was to evaluate the effect of treatment through laser therapy and resisted exercise in neuropathic pain. An experimental study of neuropathic pain induced by the average compression of 0.33kgfm in the common trunk of the sciatic nerve in the rattus norvegicus albinus, with random division between laser and exercise groups. In order to investigate the laser effect and resistance exercise, behavioral tests were carried out to evaluate the degree of thermal hyperalgesia, mechanical alodynamics and locomotor activity, in addition to determining concentrations of protein and reactive and hemogram. The application of the laser was performed with the dose 808 nm and fluency of 4J / cm2 in the middle third of the scar caused by the induction of DN. Regarding weathered exercise, 4 series of 15 repetitions with 15 seconds of pause on alternate days were performed, totaling 10 applications. After the induction of the DN the animals were distributed according to treatment in: group Sham (n = 6) treated with 0.9% physiological serum, and the intervention group was subdivided into 3 subgroups: the laser group (n = 6 ); Resisted exercise group (n = 6); The positive control group (pregabalin) (n = 6) received the dose of oral (1mL / kg). Behavioral tests were performed for analysis of nociception and laboratory analysis of protein C reactive (qualitative test), complete blood count. For statistical analysis of the results, the Graph Pad Prism software was applied using the ANOVA test and the Turkey test. In relation to behavioral evaluation through Grimace Scale mouse was observed that the laser group had significant improvement from D3, with statistical difference between laser groups and resisted exercise in relation to the saline group. In relation to march compromise, it was possible to observe the group treated with resisted exercise and laser therapy only presents statistically significant improvement from the twenty-first day by maintaining until the end of the evaluation period. In the analysis of weight distribution, it was possible to observe a statistically significant difference between the treated groups when compared to the saline group. As for the nociceptive threshold of paw withdrawal there was an increase in the nociceptive threshold in all the groups studied, however, there was no statistically significant difference from the groups treated with laser therapy and resisted exercise in relation to the saline treated group. The evaluation of thermal hyperalgesia was observed that laser-treated groups and physical activity presented a statistically significant difference from the group treated with saline from the decimo fourth day of observation. In relation to the hemogram, no changes were detected in the groups studied, already in determining the protein concentration C reactive, only the pregalin treated group had altered levels. The results of this study suggest that the application of the laser therapy at the dose of 4J / cm2 and the weathered therapeutic exercise improved spontaneous pain, weight distribution and thermal nociception the neuropathic pain in rats.